PEWARTAAN DAN KETERBUKAAN ISLAM DAN KATOLIK TINJAUAN PENDAMAIAN MENURUT ILMU PERBANDINGAN AGAMA - Marianus Ivo Meidinata (Abrahamic Religions: Jurnal Studi Agama-Agama, 2022)
In this study, the author focuses on the reconciliation between proclamation and openness, especially in Islam and Catholicism. This research is comparative research. Methods Data collection is done through a literature study. The perspective of comparative religion is taken to find the meaning of the encounter between the two teachings in Islam and Catholicism. This study finally came to the conclusion that both Islam and Catholicism have their own understanding and teachings regarding preaching and openness. In preaching, both religions believe that da'wah/mission is carried out as a form of transmitting teachings as well as carrying out Allah's commands (through the Prophet Muhammad and Jesus Christ). Both religions believe that their way is the truth. Differences in understanding are more visible in the motives for the openness of each religion. Three guidelines are needed in carrying out da'wah or preaching missions, namely the understanding that humans have ratios, the need for understanding the teachings of other religions, and the importance of an attitude of peace. One concrete activity that needs to be done is interreligious dialogue. When religious adherents adhere to and carry out these principles and activities, then everyone is able to continue carrying out the task of preaching (da'wah/mission) as well as being open to the reality of differences